The portrait of the underground economy and tax evasion: Descriptive analysis from border region - Aloysius Hari Kristianto; Pramatatya Resindra Widya; Jones Parlindungan Nadapdap (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2021)
Underground economic activity is a phenomenon that requires special and continuous treatment. This phenomenon is counterproductive to local revenues and is related to corrupt practices and tax evasion. The research was conducted in Bengkayang Regency, West Kalimantan Province, Indonesia. The qualitative phenomenological method was carried out by interviewing underground economic actors such as liquor producers, "pangku" coffee shops, and street vendors. The findings indicate that corruption activities in the form of collecting bribes and offering bribes are carried out in cash without going through a legal transaction mechanism. The underground economy practices tax evasion, does business without a permit, pays substandard wages, and does not protect workers with insurance.  The underground economic activity will contribute to an increase in the circulation of money in society, but do not take into account the regional economy. Such situations call for massive supervision of individuals and the introduction of pentahelix elements to form synergies between actors and to begin to integrate and develop digital structures in every financial activity using e-government systems.JEL Classification  D73; E26; O17